PERILAKU NYAMUK MANSONIA DAN ANOPHELES SERTA HUBUNGANNYA DENGAN PENYAKIT FILARIASIS DI KECAMATAN TANIWEL TIMUR DAN TANIWEL KABUPATEN SERAM BAGIAN BARAT - Rehena, Johanis F; Matdoan, Muhammad Nur; Rehena, Zasendy (Program Studi Pendidikan Biologi FKIP Unpatti, 2021)
Background: Mansonia mosquitoes are in endemic forest and swamp areas, dirty environments andunused fish farming areas, Mansonia mosquitoes are aggressive and suck blood when humans are at night,outside the home. Anopheles actively seeks blood during illness and at night.Methods: This research uses survey and cross sectional research, it discusses to study mosquitoes, thedensity of mosquitoes mansonia and anopheles, as well as looking at the development of disease(prevalence) of filariasis. The population in this study is the population and population of mosquito mansoniaand anopheles in East Taniwel and Taniwel Districts. Filariasis in Taniwel and East Taniwel Sub-districts,West Seram District was reported in local health centers of around 15 people. The outbreak of filariasis inTaniwel District around 2010-2019.Result: Mansonia mosquitoes bleeds people at home when sick at 18: 00-18: 45. While outside the houseat night 20: 00-20: 45. While Anopheles mosquitoes bite humans, at dusk and at night at 16.00-24.00, Thepeak is 02.00-03.00. The density of mansonia mosquitoes in Sohuwe Village, 4.00 - 5.85, Lumalatal 5.00 -6.60 and Maloang 4.00-5.50 (moderate), Anopheles in Sohuwe 7.00-9.85, Lumalatal 5.89- 6.82, Maloang5.00-6.50 (high).Conclusion: The prevalence of filariasis in Sohuwe 0.66, Lumlat 0.88. and Maloang 1.54. There is arelationship between attitudes and community relations with filariasis.